Assessment of the anaerobic speed reserve during specific high-intensity exercise in judo athletes - Franchini, E.; Kons, R. L.; Panissa, V. L. G.; Detanico, D. (Journal of Science in Sport and Exercise, 2022)
Purpose: This study aimed to describe self-selected intensity and its relationship to performance during a high-intensity all-out judo protocol, and to verify whether athletes with different anaerobic speed reserve (ASR) perform differently during a high-intensity all-out interval uchi-komi (judo-specific skill). Methods: We analyzed the performance of 28 judo athletes as a whole group and divided into groups, according to their ASR. They performed several judo-specific protocols using a specific skill: maximal speed sprint (MSS) and maximal aerobic speed (MAS), and high-intensity intermittent uchi-komi protocol (12 × 20 s all-out:10 s passive recovery). Results: The main results demonstrated a decrease in the number of repetitions and an increase in heart rate across the sets. Athletes with greater ASR performed a higher number of repetitions, compared to the low ASR group, and they were able to exercise at a higher percentage of the MAS (low ASR = 126%; SD = 13%; high ASR = 152%, SD = l9%) and at a lower percentage of MSS compared to the low ASR group (low ASR = 84%, SD = 7%; high ASR = 76%, SD = 11%). However, both groups exercised at a similar percentage of their own ASR during the protocol (low ASR = 50%, SD = 20%; high ASR = 53%, SD = 19%). Conclusions: Athletes with different ASR seem to set their pace at around 50% of their ASR within an all-out uchi-komi protocol. Therefore, the ASR is useful for predicting performance during high-intensity judo-specific interval exercise intervals.